2019
DOI: 10.21058/gjecs.2019.41001
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Scaled Green Data Flip Flop on Different Nanometer Technology Based FPGA

Abstract: In order to meet the energy requirement of the total population of the globe, we have designed an energy efficient data flip flop on different nanometer technology-based FPGA. We used frequency scaling technique in order to analyze power dissipation. The power has been analyzing for Virtex 6 (40nm) FPGA, Spartan 3 (90nm) FPGA, Spartan 6 (45nm FPGA). We varied the frequency from 10 MHz to 100 GHz and observed the different powers of chips which are clustered on data flip flop, e.g. Clocks, Signals, I/O, Leakage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To promote the ideas of green communication researchers have implemented a power-efficient CU on Virtex and Spartan family's FPGA (Pandey, 2020). An energyefficient CU is designed by authors with the help of HSTL and HSUL I/O standard for green communication on 28nm Artix-7 FPGA devices (Kumar, Pandey, & Chaturvedi, 2019e). An energy-efficient instruction register is designed by authors for integrating the green communication on Virtex 4, Virtex 5, and Virtex 6 FPGA (Siddiquee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To promote the ideas of green communication researchers have implemented a power-efficient CU on Virtex and Spartan family's FPGA (Pandey, 2020). An energyefficient CU is designed by authors with the help of HSTL and HSUL I/O standard for green communication on 28nm Artix-7 FPGA devices (Kumar, Pandey, & Chaturvedi, 2019e). An energy-efficient instruction register is designed by authors for integrating the green communication on Virtex 4, Virtex 5, and Virtex 6 FPGA (Siddiquee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for lower clocks, data transfer was impractical. Power analysis was performed using Vertex-6, Spartan 3, and Spartan 6 FPGAs in [4] for various frequencies from 10MHz to 100MHz. It was concluded that the power dissipation was less at low frequency, and at high frequency, the power was high.…”
mentioning
confidence: 99%